2009
DOI: 10.1007/s10798-009-9086-8
|View full text |Cite
|
Sign up to set email alerts
|

Question-answering-technique to support freshman and senior engineers in processes of engineering design

Abstract: In two experimental studies, the influence of question-based reflection on the quality of design solutions was investigated. Students and experts with different know-how and professional experience had to design an artefact that should meet a list of requirements. Subsequently, they were asked to answer a system of interrogative questions stimulating reflection on the solutions with the opportunity to modify or revise them. These questions cause the participants to explain, justify and evaluate their finished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Chen and Kanfer (2006) point out that the explicit generation and formulation of team goals is a necessary motivational process that influences later team behaviour. In STROTA, individual situation awareness, team situation awareness, and plan formulation apply a questionanswering technique (Wetzstein & Hacker, 2004;Winkelmann & Hacker, 2010). This method provides guidance for reflection about the given feedback and the development of future action plans.…”
Section: Structured Online Team Adaptation 815mentioning
confidence: 99%
“…Chen and Kanfer (2006) point out that the explicit generation and formulation of team goals is a necessary motivational process that influences later team behaviour. In STROTA, individual situation awareness, team situation awareness, and plan formulation apply a questionanswering technique (Wetzstein & Hacker, 2004;Winkelmann & Hacker, 2010). This method provides guidance for reflection about the given feedback and the development of future action plans.…”
Section: Structured Online Team Adaptation 815mentioning
confidence: 99%
“…causal, conditional or final ones) within any system and, thus, initiating reflective thinking on the completeness of the analysis and the significance of the requirements. Albeit the efficiency of the isolated GQAS was repeatedly verified (Wetzstein and Hacker 2004;Winkelmann and Hacker 2009), it has so far remained unknown whether a GQAS contributes additional benefits if applied together with a proven technical check list as offered in engineering textbooks (Lindemann 2007;Pahl et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental research has shown that control groups without the GQAS identified significantly less requirements than experimental ones with the GQAS (Winkelmann and Hacker 2007). Moreover, other experimental studies with students of engineering design and with experienced designers revealed significantly better design solutions in groups using the list of interrogative generic questions aimed at the ''semantic relationships'' (Wetzstein and Hacker 2004;Winkelmann and Hacker 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Question-answering techniques proved useful as a generic cognitive strategy in a series of experimental studies demonstrating significant improvements in the quality of design solutions of medium effect size ('C-QuARK', Ahmed et al, 2000;Winkelmann and Hacker, 2010). This beneficial effect persists even if the set of questions is applied along with specific checklists supporting the analysis of engineering-specific requirements (Winkelmann and Hacker, 2011).…”
Section: Generic Cognitive Strategies Supporting the Early Phases Of mentioning
confidence: 99%